Gallium‐Doping Effects on Structure, Lithium‐Conduction, and Thermochemical Stability of Li7‐3xGaxLa3Zr2O12 Garnet‐Type Electrolytes. Issue 12 (13th May 2021) - Birkner, Nancy; Li, Changlong; Estes, Shanna L.; Brinkman, Kyle S.
Abstract: One of the most promising electrolytes for all‐solid‐state lithium batteries is Li7 La3 Zr2 O12 . Previously, their thermodynamic stability, Li‐ion conductivity, and structural features induced by Ga‐doping have not been empirically determined or correlated. Here, their interplay was examined for Li7−3 x Ga x La3 Zr2 O12 with target x Ga=0, 0.25, 0.50, 0.75, and 1.00 atoms per formula unit (apfu). Formation enthalpies, obtained with calorimetry and found to be exothermic at all compositions, linearly decreased in stability with increased x Ga. At dilute x Ga substitution, the formation enthalpy curve shifted stepwise endothermically, and the conductivity increased to a maximum, coinciding with 0.529 Ga apfu. This correlated with percolation threshold analysis (0.558 Ga apfu). Further substitution (0.787 Ga apfu) produced a large decrease in the stability and conductivity due to a large increase in point defects and blocked Li‐migration pathways. At x Ga=1.140 apfu, a small exothermic shift was related to defect cluster organization extending the Li hopping distance and decreased Li‐ion conductivity. Abstract : How much dopant ? This is the first work to correlate Li‐ion conductivity and diffusion coefficients, Li‐vacancies, Ga‐doping, and experimental thermochemistry in Ga‐doped LLZOs. Low concentration doping produces defects that promote conductivity and stepwise endothermic formation enthalpy changes. Concentrated dopant yields poor conductivity and increased defect formation (endothermic shift). Further, an increase results in defect clustering (exothermic contributions).